Advancing across boundaries: Expanding footprint and impact of RIICE technologies in Africa - Quicho, Emma; Raviz, Jeny; Murugesan, Deiveegan; Satapathy, Sushree; Maunahan, Aileen; Gatti, Luca; Holecz, Francesco; Dossou-Yovo, Elliot; Mathieu, Renaud (International Rice Research Institute, 2023)
Rice production in Africa has been steadily increasing over the years driven by a growing population, changing dietary preferences, and continuous efforts to enhance food security on the continent. However, local production covers only 60% of the current demand, resulting to ~ 14-15 MT rice importation. Recently, the Remote-sensing based Information and Insurance for Crops in emerging Economies (RIICE, http://www.riice.org/) is being introduced across Africa to enhance the rice monitoring system. RIICE technology is a public-private partnership aimed at strengthening food security and reducing the vulnerability of small rice farmers, by providing timely and accurate information on rice crops and supporting the design of crop insurance schemes to protect farmers against potential crop losses due to natural disasters.